Pré-validação da Behavioural Assessment of the Dysexecutive Syndrome (BADS) para uma amostra com perturbações por uso de substâncias ilícitas-álcool - Cerqueira, Ana Angélica Rodrigues (2018)
The BADS is a neuropsychological evaluation tested aimed to diagnosie executive function deficits in general or in specific components of it. Several studies indicated that the executive functioning is the most harmed by psychoactive substance´s consumption. Thus, the purpose of this study is to analyse the BADS psychometric qualities, on a sample of individuals with alcohol and ilicit substance use disorder, using concurrent and convergent validity, as well analyse Dex Questionnaire´s internal consistency. This study´s sample is constituted by 35 participants, of whom 88,6 % are males, with an average age of 44,45 years. It was confirmed that BADS is significantly related with general cognitive performance, showing to be good concurrent validity indicador and significantly correlated with FAB, suggesting to be convergent validity indicators. It was also confirmed that, the individuals with lower schooling degree, have an inferior cognitive´s flexibility and general function performance. The results suggest that the BADS is a useful and valid neuropsychological battery to evaluate executive functioning in inviduals with disruption due to the use of ilicit substances and alcohol.